Stany nadzwyczajne z perspektywy prawa publicznego gospodarczego - Nowicki, Henryk; Brzeziński, Mateusz (PRAWO i WIĘŹ, 2025)
This paper examines the issue of states of emergency from the perspective of public economic law, with particular emphasis on constitutional issues and public procurement law. Public economic law aims to protect the fundamental values of a market economy, such as freedom of economic activity and private property, which may only be restricted by law and only for reasons of important public interest. The introduction of states of emergency allows the state to temporarily interfere with these freedoms to a far-reaching extent, which may result in an increase in the powers of the state at the expense of entrepreneurs and the risk of perpetuating emergency regulations. At the same time, the Constitution imposes on the state an obligation to act proportionately, to limit the duration of such measures and to take into account the principles of compensation, although legislative practice shows that ‘special laws’ are often used to evade these restrictions. Public procurement law is intended to ensure transparency, competitiveness and efficiency in the spending of public funds, but in emergency situations, the lawmakers often introduce special laws that completely exclude the application of these procedures. Such solutions increase the discretion of the administration at the cost of contractors, limiting competition and preventing the achievement of both procurement and non-procurement objectives of public contracts. The lack of intermediate mechanisms (e.g. shortened procedures) and the abuse of total exemptions from the application of the Public Procurement Law may lead to a market imbalance and the risk of discretionary spending of public funds, which should be assessed in the light of the principle of proportionality.